2013
DOI: 10.1371/journal.pone.0068396
|View full text |Cite|
|
Sign up to set email alerts
|

Adult Cardiac Expression of the Activating Transcription Factor 3, ATF3, Promotes Ventricular Hypertrophy

Abstract: Cardiac hypertrophy is an adaptive response to various mechanophysical and pathophysiological stresses. However, when chronic stress is sustained, the beneficial response turns into a maladaptive process that eventually leads to heart failure. Although major advances in the treatment of patients have reduced mortality, there is a dire need for novel treatments for cardiac hypertrophy. Accordingly, considerable efforts are being directed towards developing mice models and understanding the processes that lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…Interestingly, cardiac-specific expression of both JDP2 and ATF3 during embryonic period results in atrial enlargement and premature death in transgenic mice [25][26][27]. In contrast, adult ATF3 expression is sufficient to induce ventricular hypertrophy even in the absence of additional insults such as pressure overload [27]. In line with these studies, ATF3 was found to be required for cardiomyocytes growth response to endothelin-1 stimulation [28].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Interestingly, cardiac-specific expression of both JDP2 and ATF3 during embryonic period results in atrial enlargement and premature death in transgenic mice [25][26][27]. In contrast, adult ATF3 expression is sufficient to induce ventricular hypertrophy even in the absence of additional insults such as pressure overload [27]. In line with these studies, ATF3 was found to be required for cardiomyocytes growth response to endothelin-1 stimulation [28].…”
Section: Introductionmentioning
confidence: 64%
“…All mice genotypes were backcrossed to C57Bl/6 background for at least 8 generations. Mice used in this study: ATF3-KO [33], ATF3-KO Flox [34] and αMHC-CRE mice [35], ATF3-Tg and αMHC-tTA [27]. Male mice were used in all the experiments performed in this study unless otherwise specified.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…ATF3 can act as either a transcriptional activator or repressor, and is involved in the rapid regulation of many genes (26). Under normal conditions, ATF3 is not detectable in the heart, but is induced rapidly following myocardial ischemia (4,28).…”
mentioning
confidence: 99%
“…Indeed, cardiac ATF3 overexpression may be sufficient to provoke conduction abnormalities and contractile dysfunction (28). Furthermore, ATF3 overexpression in otherwise healthy adult mice produces cardiac fibrosis, cardiac hypertrophy, and cardiac dysfunction (26); adult ATF3 overexpressing mice are also more susceptible to pressure overload-induced cardiac dysfunction, and complementary loss of function studies demonstrated that ATF3 deficiency reduces cardiomyocyte hypertrophy and protects the heart against pressure overload (26). Conversely, others have shown that ATF3 deficiency enhances cardiomyocyte hypertrophy in vitro, and ATF3 deficiency exacerbates cardiac fibrosis in a pressure overload model (40).…”
mentioning
confidence: 99%